Pengaruh IPM, Biaya Infrastruktur, Investasi dan Pertumbuhan Ekonomi Terhadap Ketimpangan Distribusi Pendapatan di Provinsi Bali - Pradnyadewi, Diah; Purbadharmaja, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 2, Februari 2016 (pp. 115 - 285), 2017)
Unequal distribution of income can be caused by several factors, including uneven amount of quality human resources, infrastructure costs and investment in an area. This research has a purpose to analyze directly effect and indirectly effect of  HDI, infrastructure costs and the investment of the unequal distribution of income through economic growth in the district/city in Bali. This research uses secondary data from 2008 – 2015. The method used in this research is a non-participant observation data collection and in this research used path analysis. In this research found that HDI has directly and significant impact on economic growth. Infrastructure costs and economic growth have directly and significant effect on the unequal distribution of income. Meanwhile, HDI and investment have not significant effect on inequality of income distribution. Economic growth is a variable intervening the indirect influence of the HDI and infrastructure costs of the unequal distribution of income.
Keywords: ketimpangan distribusi pendapatan; IPM; biaya infrastruktur; investasi; pertumbuhan ekonomi